Teofil Myronovich Pidlisetsky - Staff of SI «SISJP NAMS», - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 70th anniversary of the birth of the Honored Doctor of Ukraine, the famous orthopedist traumatologist, talented surgeon Pidlisetskogo T. M.